Child to parent violence: From mistreatment to bad treatment - Iglesias Huerga, Israel (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2018)
Child to parent violence is not only a relevant reality, but also an increasing problem in our current society. This type of violence causes a high impact both on the young person’s life and on their family and social environment. Due to its multi-causal nature, addressing this reality must be done taking into account a series of key aspects like the personality of all the members involved, the relational dimensions of the system or the development and performance in other operational spheres.  Adolescence is, per se, a convulsive stage that entails a certain degree of confrontation and unrest in their most creative processes. A situation specially enhanced when other circumstances hindering the young person’s development concur during this period, thus making it far more complex. Both research on and direct intervention with children and young persons who carry out episodes of child-to-parent violence allows us to identify different aspects that in some way exert an influence and feed the problem.  Amongst these it is quite frequent to identify the following: difficulties in the impulse control, limited tolerance towards frustration, abandonment feelings, high insecurity, migration processes or traumatic separations, emotional illiteracy, inability to handle with feelings of guilt or even drug use.
Keywords: child-to-parent violence; adolescence; mistreatment